PENGUKURAN KEPUASAN NASABAH TERHADAP CUSTOMER SERVICE PADA PT BANK RAKYAT INDONESIA (PERSERO) Tbk, PEMBANTU KAYU TANGI BANJARMASIN - Nurchosyanti Nurchosyanti; Rika Novyanti; Novi Shintia (At-Tadbir : jurnal ilmiah manajemen, 2019)
Banks as financial services sector must absolutely pay attention to the quality of service to their customers. The service performed is a form of the best service provided by a bank to provide satisfaction to customers. The purpose of this study was to determine the level of customer satisfaction with the service of Customer Service of PT Bank Rakyat Indonesia (Persero) Tbk, the Banjarmasin branch of Kayu Tangi. This study uses a descriptive qualitative approach, which is to give an overview of the events studied so that it is easier for writers to get objective data in order to know and understand how employee motivation affects performance. The population in this study is the customer who made the main transaction in the Customer Service section of PT Bank Rakyat Indonesia (Persero) Tbk, Banjarmasin Tangi Wood Branch Office. Samples are taken randomly and are considered to represent the answers of all customers in the bank. The number of samples taken was 80 respondents. The results of this study indicate that the measurement of customer satisfaction with Customer Service at PT Bank Rakyat Indonesia (Persero) Tbk, Kayu Tangi Banjarmasin Sub-Branch Office still needs to be developed because there are some criticisms from customers of the servqual dimensions namely, Tangible, Reliability, Responsiveness, Assurance and Empaty. Keywords: Customer Satisfaction, Customer Service, Service Quality, Customer and Service